Uma estimativa da função de produção no setor sucroalcooleiro utilizando microdados de custo - Rocha, Sálvio Pontes Moreira (2013)
Productivity is often calculated by the approach of the Cobb-Douglas production function. This estimate, however, may suffer from s imultaneity and inputs bias selection. The method of Olley and Pakes (1996) int roduced a semi-parametric method allows us to estimate the parameters of the production function consistently and thus obtain reliable measures of p roductivity, controlling such bias problems. This study applies this method in a company the sugarcane sector and uses the command opreg at Stata to esti mate the production function of a company and concluded with the econom ic intuition behind the result.